Glide Path in Endodontics: A Literature Review of Current Knowledge - Vlad Mircea Lup; Giulia Malvicini; Carlo Gaeta; Simone Grandini; Gabriela Ciavoi (MDPI AG, 2024)
The introduction of nickel-titanium rotary instruments revolutionized shaping procedures as they were able to produce a well-tapered preparation while reducing operator fatigue. The major drawback of rotary instruments was the high risk of fracture due to bending and torsional stress. Thus, the creation of a glide path has been advocated and recommended by most rotary instrument manufacturers. The aim of the present review is to summarize existing knowledge on glide path preparation and identify areas where further research is needed. The primary goal is to provide a comprehensive overview of the techniques and instruments used in glide path preparation, highlighting their advantages and limitations. The secondary goal is to explore the effect of glide path creation on the overall success of endodontic treatment, particularly in terms of reducing procedural errors and improving treatment outcomes. An online search on PubMed, ScienceDirect, UCLA, and Scopus databases was conducted, and 116 articles were identified. Eligible articles were divided into nine categories based on what they researched and compared. The categories included centering ability and/or root canal transportation, cyclic fatigue resistance, glide path and shaping time, tortional stress resistance, apical extrusion of debris and/or bacteria, defects in dentine walls, file separation, postoperative pain assessment, and scouting ability and performance. Establishing a glide path reduces root canal transportation, especially with rotary methods. Reciprocating and heat-treated files offer higher fatigue resistance and shorter preparation time. Instruments with shorter pitch lengths have greater torsional strength. Preparation and coronal preflaring reduce apical debris and bacteria. Glide paths do not affect dentine microcracks, file separation, or defects but reduce immediate postoperative pain and improve cutting ability. Randomized trials are needed to assess their impact on treatment outcomes.